Pengaruh Budaya Organisasi dan Komitmen Organisasi terhadap Kinerja Karyawan PT. Taman Sari Boga Catering - Adella Fakhira Mauludia; Suroso; Flora Patricia Anggela (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze the influence of organizational culture and organizational commitment partially and simultaneously on employee performance at PT. Taman Sari Boga Caterin, the location of the company is in West Adiarsa, Karawang. The method used was quantitative verification techniques with a sample of 35 PT respondents. Taman Sari Catering Catering. This sampling method uses a saturated sampling method. The analysis model using multiple regression analysis maximizes the results of the F test and t test, a significance level of 5%. Research findings show that organizational culture partially influences the performance of PT employees. Taman Sari Boga Catering with a value of (1.500 > 0.361). Partial organizational commitment greatly influences the performance of PT employees. Taman Sari Boga Catering with a value of (2.496 > 0.361). Meanwhile, organizational culture and organizational commitment simultaneously influence the performance of PT Taman Sari Boga Catering employees because the calculated F value is 14.857 > 3.29. Results of the influence of organizational culture and organizational commitment on the performance of PT employees. Catering Taman Sari Boga Catering amounted to 0.489 or 48.9%, apart from that the remainder was due to the influence of other factors that were not examined, namely 0.511 or 5.11%.